Tueng Bila as a characteristic and identity of Acehnese culture - Wibowo, Agus Budi (Universiti Kebangsaan Malaysia, 2014)
Tueng Bila is one of the characteristics and identities of Acehnese cultural values, usually expressed as a form of violence against another person, either individually or in a group. This research was conducted to understand the meaning and motives behind such actions, as a way of proposing a solution for ending violence undertaken in this way. This research explores the importance of Tueng Bila as an integral part of Acehnese culture, using data obtained through oral interviews with informants in addition to a literature review. Based on the results of this research, Tueng Bila can be interpreted as targeted action, often taking the form of a revenge attack against a family or individual that occasionally results in death. Tueng Bila is culturally justified, but it is often performed without arbitrary reason, and it is strongly associated with the self-esteem of a person, family or kawom; in Acehnese, human. However, in Acehnese culture, there is also a mechanism for conflict resolution that involves enacting local policy. By this method, local policy mechanisms extract a guilty plea and payment of compensation as a way to eliminate ongoing hostility between the warring parties. It can be seen then, that on the one hand there is a culture of violence in Acehnese society, but on the other hand there are indigenous mechanisms available to mediate disputes that have traditionally been practiced by the community.